2018
DOI: 10.1016/j.bjm.2017.04.010
|View full text |Cite
|
Sign up to set email alerts
|

Contribution of dark septate fungi to the nutrient uptake and growth of rice plants

Abstract: The use of dark septate fungi (DSE) to promote plant growth can be beneficial to agriculture, and these organisms are important allies in the search for sustainable agriculture practices. This study investigates the contribution of dark septate fungi to the absorption of nutrients by rice plants and their ensuing growth. Four dark septate fungi isolates that were identified by Internal transcribed spacer phylogeny were inoculated in rice seeds (Cv. Piauí). The resulting root colonization was estimated and the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
63
2
2

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 67 publications
(71 citation statements)
references
References 63 publications
4
63
2
2
Order By: Relevance
“…On the other hand Ascomycota is known to include "dark septate endophytes" (DSEs) and has been observed in roots of plants that grow in stressful and nutrient-limited [52] and have shown a positive effect on plant growth [53,54] probably because of nitrogen mineralization and pathogen protection [55].…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand Ascomycota is known to include "dark septate endophytes" (DSEs) and has been observed in roots of plants that grow in stressful and nutrient-limited [52] and have shown a positive effect on plant growth [53,54] probably because of nitrogen mineralization and pathogen protection [55].…”
Section: Discussionmentioning
confidence: 99%
“…It has been suggested that DSEs mineralise proteins and peptides in the soil, making N more available for uptake by roots (Upson et al 2009). Although the reciprocal nutrient transport between DSEs and plants has been proven (Usuki and Narisawa 2007;Porras-Alfaro and Bayman 2011), and the contribution of DSEs to N uptake has been studied in detail (Usuki and Narisawa 2007;Upson et al 2009;Porras-Alfaro and Bayman 2011;Vergara et al 2017Vergara et al , 2018, the mechanisms behind the effects of those root colonisers on their hosts are not well understood. Generally, root-associated fungi can mobilise different nutrients and help the uptake of these nutrients by plants or bridge nutrient depletion zones and transport the nutrients via hyphae to the roots (Behie and Bidochka 2014;Souza et al 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Certain Ascomycota including DSE form mycorrhizae in plant roots and enhance plant nutrient uptake and growth [37,38]. Lin et al [39] found that Ascomycota, Basidiomycota, and Zygomycota strongly tolerated heavy metal contamination. Moreover, Proteobacteria, Actinobacteria, Chloro exi, Firmicutes, and Acidobacteria predominated in the licorice rhizosphere under drought stress regardless of DSE inoculation.…”
Section: Discussionmentioning
confidence: 99%